PENGARUH HAMBATAN SAMPING TERHADAP KINERJA ARUS LALU LINTAS DI JALAN RAYA AHMAD YANI SARIO MANADO - Hizkia Diego Polii; Toar U. Y. Pangkey; Tendly S. Maki (Sustainable Construction (SUSCON), 2024)
The purpose of this study is to determine the side barriers on the Ahmad Yani road. The results of this study were carried out by direct observation at the research location. The research results show that the highest traffic volume occurs in the afternoon, in passenger car units (pcu/hour), the highest traffic flow is obtained on Tuesday at 15.00-16.00 at 2938.2 pcu/hour. The highest calculated side barriers are on Tuesdays at 15.00-16.00 in 1 hour, namely 513.9 events/hour which is included in the High (H) side resistance class, so that the total value of the degree of saturation is 0.9832 where the level of service E The flow is unstable, the volume is close to capacity, the speed is low and sometimes stops. Based on the problem of side obstacles, the way that needs to be done is to make regulations in the form of a prohibition against parking carelessly on the road, especially on the side of the road, by providing sanctions for those who violate it. as well as making road markings and special signs for pedestrians.